Development of a methodology for artificial intelligence-based clustering of stow and pick operations in order to improve logistics performance in small and medium-sized enterprises - Schroth, Timo Friedrich (Stellenbosch : Stellenbosch University, 2025)
Schroth, T. F. 2025. Development of a Methodology for Artificial Intelligence-based Clustering of Stow and Pick Operations in order to Improve Logistics Performance in Small and Medium-sized Enterprises. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/45918fc0-abbc-4876-89ea-e653d2cad76a